Umpan Balik Sistem Pakar sebagai Penilaian Kinerja Karyawan pada PT. Multistrada Arah Sarana, Tbk - Eneng Iviq Hairo Rahayu; Suhardoyo Suhardoyo; Iwan Iwan (Universitas Muria Kudus, 2019)
In this study the researcher described the expert system-based feedback as performance assessment for the employees at PT Multistrada Arah Sarana, Tbk. By using descriptive qualitative research, purposive sampling technique is used in this research to determine the people who will be used as resource persons. The data analysis technique used in this study is the interactive model. The variables used in this study were feedback and performance assessmentOne important factor is giving feedback or review in the production process. The aim is to keep the production process running well and smoothly to produce number of targeted items to meet market needs. Evidence-based performance management relies on feedback that relies on facts rather than opinions. Giving the type of feedback must be tailored to the needs of employees. Employee needs are related to the level of psychosocial development of employees.Feedback can be delivered by the competent facilitator so that recipients of feedback can find out their strengths and weaknesses. Using the feedback employee can then set future goals and improvement targets so that their leadership performance becomes more effective. In order to record feedback and follow up on the implementation of objectives that have been made related to the feedback provided, it is better if the manager of the talent management program provides a book that specifically records the track record of the participants